The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1128/aac.04986-14
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Lysophosphatidylcholine in Severe Infections Caused by Acinetobacter baumannii

Abstract: bDue to the significant increase in antimicrobial resistance of Acinetobacter baumannii, immune system stimulation to block infection progression may be a therapeutic adjuvant to antimicrobial treatment. Lysophosphatidylcholine (LPC), a major component of phospholipids in eukaryotic cells, is involved in immune cell recruitment and modulation. The aim of this study was to show if LPC could be useful for treating infections caused by A. baumannii. A. baumannii ATCC 17978 was used in this study. Levels of serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 25 publications
4
53
0
Order By: Relevance
“…Previous studies from our group demonstrated that preemptive LPC therapy protected mice from A. baumannii infections, reducing bacterial organ loads and bacteremia and increasing mouse survival to 40% (14), similar to the results obtained with both strains used in the present study. In addition, we showed that surviving mice had lower bacterial burdens in tissues than those in dead mice, which explains the observed improvement in survival.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Previous studies from our group demonstrated that preemptive LPC therapy protected mice from A. baumannii infections, reducing bacterial organ loads and bacteremia and increasing mouse survival to 40% (14), similar to the results obtained with both strains used in the present study. In addition, we showed that surviving mice had lower bacterial burdens in tissues than those in dead mice, which explains the observed improvement in survival.…”
Section: Discussionsupporting
confidence: 91%
“…A previously characterized murine model of peritoneal sepsis caused by A. baumannii was used (14). Briefly, animals were inoculated i.p.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although LPCs are typically regarded as pro-inflammatory mediators, they were increased in inflammatory diseases (27,28). A previous series of studies have demonstrated a protective effect of LPCs against diseases, including type 2 diabetes (29), cancer (30) and inflammatory diseases (31).…”
Section: Trend ------------------------------------------------------mentioning
confidence: 99%